Cost-Optimal measures for renovation of existing school buildings towards nZEB. (December 2017) - Mora, T. Dalla; Righi, A.; Peron, F.; Romagnoni, P.
Abstract: The energy policies of the European Union (EU) encourage the member states to convert building stock into nearly Zero-Energy Buildings (nZEB) and national public authorities to adopt exemplary actions. Directive 2010/31/EU (EPBD recast) introduces the concept of nZEB as a building that has a very high energy performance and its energy need is covered to a very significant extent by energy from renewable sources (RES). Moreover the Directive refers to the cost-optimal methodology for fixing building energy requirements. This paper presents the results of the application of the cost-optimal methodology in a couple of existing school buildings located in the North East of Italy. The analysed buildings are a primary and a secondary schools that differ in construction period, in compactness ratio, in buildings envelope materials and systems. Several combinations of retrofit measures have been applied in order to derive cost-effective efficient solutions for retrofitting according to the methodology proposed by the project Annex56 "Cost Effective Energy & CO2 Emissions Optimization in Building Renovation". The cost-optimal level has been identified for each building and the best performing solutions have been selected considering a financial analysis and the application of "Conto Termico 2.0" government incentives. The results show the suitability of the proposed methodology to assess cost-optimality and energy efficiency in school building refurbishment. Moreover, this study shows different possibility providing the most cost-effective balance between costs and energy saving.